A Condensed Course of Quantum Mechanics. - Cejnar, P. (Pavel) (Charles University in Prague, Karolinum Press, 2013)
This book represents a concise summary of non-relativistic quantum mechanics on the level suitable for university students of physics. It covers, perhaps even slightly exceeds, a one-year course of about 50 lectures, requiring basic knowledge of calculus, algebra, classical mechanics and a bit of motivation for the quantum adventure. The exposition is succinct, with minimal narration, but witha maximum of explicit and hierarchically structured mathematical derivations. The text covers all essential topics of university courses of quantum mechanics - from general mathematical formalism to specif.